Effects of Addition of Protein Isolates from Jack Bean Seed (Canavalia ensiformis L.) on the Characteristics of Cake - Achmad Subagio; Wiwik Siti Windrati; Yuli Witono (Jurnal Teknologi dan Industri Pangan, 2003)
Addition of jack bean (Canavalia ensiformis L.) protein isolate in cake making was studied. The isolate was prepared from the beans by the method of isoelectrical point at pH 4. At low concentrations (less than 1% of the wheat flour), the addition of the protein isolate could improve the characteristics of the cake by increasing the loaf volume, decreasing the density, and softening the texture. In contrast, the addition of 1.5% tended to decrease the quality of the cake as compared to that added with 1% by decreasing the loaf volume, increasing the density, and hardening the texture. However, the more protein isolate added, the more slowly the rate of the cake staling. Key words : Cake, jack bean, protein isolate.